Peran Latihan Disupervisi pada Pasien dengan Penyakit Arteri Perifer Eksremitas Bawah - Lestari, Defyna; Tjahjono, Cholid (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Peripheral arterial disease is a disorder caused by decreased blood flow to the extremities. The process of atherosclerosis generally causes it and manifests as claudication. In addition to optimal medical and endovascular therapy, non-pharmacological management of PAP has been proven to be effective in reducing symptoms and improving walking ability and quality of life. Walking exercise can increase blood flow, which allows oxygen and nutrients to reach the muscles more efficiently and triggers the angiogenesis process. Supervised exercise programs in PAP patients are considered important as primary therapy to improve functional capacity and quality of life for long-term management.